Potent, Metabolically Stable 2‐Alkyl‐8‐(2H‐1, 2, 3‐triazol‐2‐yl)‐9H‐adenines as Adenosine A2A Receptor Ligands. Issue 7 (7th May 2015) - Pace, Silvia; Brogin, Giandomenico; Stasi, Maria Antonietta; Riccioni, Teresa; Borsini, Franco; Capocasa, Francesca; Manera, Francesco; Tallarico, Carlo; Grossi, Pietro; Vacondio, Federica; Bassi, Michele; Bartoccini, Francesca; et al.
Abstract Inhibition of adenosine A2A receptors has been shown to elicit a therapeutic response in preclinical animal models of Parkinson's disease (PD). We previously identified the triazolo‐9H‐purine, ST1535, as a potent A2AR antagonist. Studies revealed that ST1535 is extensively hydroxylated at the ω‐1 position of the butyl side chain. Here, we describe the synthesis and evaluation of derivatives in which the ω‐1 position has been substituted (F, Me, OH) in order to block metabolism. The stability of the compounds was evaluated in human liver microsomes (HLM), and the affinity for A2AR was determined. Two compounds, (2‐(3, 3‐dimethylbutyl)‐9‐methyl‐8‐(2H‐1, 2, 3‐triazol‐2‐yl)‐9H‐purin‐6‐amine (3 b) and 4‐(6‐amino‐9‐methyl‐8‐(2H‐1, 2, 3‐triazol‐2‐yl)‐9H‐purin‐2‐yl)‐2‐methylbutan‐2‐ol (3 c), exhibited good affinity against A2AR (Ki=0.4 nM and 2 nM, respectively) and high in vitro metabolic stability (89.5 % and 95.3 % recovery, respectively, after incubation with HLM for two hours).